2011
DOI: 10.1007/s00428-011-1124-8
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of ubiquitylation and sumoylation in conventional renal cell carcinomas after the Chernobyl accident: a comparison with Spanish cases

Abstract: We determined whether ubiquitylation and sumoylation processes are involved in conventional renal cell carcinogenesis associated with chronic, long-term, persistent low doses of ionizing radiation (IR) in patients living for more than 20 years in cesium-137 ((137)Cs)-contaminated areas after the Chernobyl accident in Ukraine. To this end, we assessed the immunohistochemical expression of ubiquitin (Ub), SUMO1, SUMO E2 conjugating enzyme Ubc9, and the cell cycle regulators p53, mdm2, and p14(ARF) in 38 conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…However, the above considerations do not only pertain to TC. The following was stated about renal cell carcinoma (RCC): "Recent studies have shown that during the period subsequent to the nuclear Chernobyl accident (April 1986), an increase in morbidity (4.7 to 9.8 per 100,000 of the total population), aggressiveness, and proliferative activity of RCC from Ukrainian patients is recognized" (Morell-Quadreny et al 2011). The increase in "aggressiveness" of the RCC was probably caused by detection in Ukraine of previously neglected cancers by means of improved diagnostic methods.…”
Section: Tnmmentioning
confidence: 99%
“…However, the above considerations do not only pertain to TC. The following was stated about renal cell carcinoma (RCC): "Recent studies have shown that during the period subsequent to the nuclear Chernobyl accident (April 1986), an increase in morbidity (4.7 to 9.8 per 100,000 of the total population), aggressiveness, and proliferative activity of RCC from Ukrainian patients is recognized" (Morell-Quadreny et al 2011). The increase in "aggressiveness" of the RCC was probably caused by detection in Ukraine of previously neglected cancers by means of improved diagnostic methods.…”
Section: Tnmmentioning
confidence: 99%
“…In addition to the pathways above, we must also emphasize the potential role of SUMOylation in metabolic reprogramming in hypoxia‐induced renal injury, as a result of recent discoveries linking the pathogenesis of kidney fibrosis to EMT, cell cycle arrest, and defective metabolism . Substantial evidence is building that SUMOylation of key regulators of metabolism may represent a newly discovered strategy by which cells protect themselves during metabolic stress.…”
Section: Discussion and Perspectivementioning
confidence: 99%
“…In addition to the pathways above, we must also emphasize the potential role of SUMOylation in metabolic reprogramming in hypoxia-induced renal injury, as a result of recent discoveries linking the pathogenesis of kidney fibrosis to EMT, cell cycle arrest, and defective metabolism. [112][113][114][115][116] Substantial evidence is building that…”
Section: Discussion and Perspectivementioning
confidence: 99%
“…Considering the above, the results of some studies are interpretable but would benefit from re-evaluation. For example, the following ISSN: 2471-4879 has been reported: "These findings do not allow us to consider the immunohistochemical expression of ubiquitylation and sumoylation as valuable markers for discriminating the effects of long-term, lowdose ionizing radiation exposure in conventional renal cell carcinoma carcinogenesis" [63]. Considering that cancers from Ukraine were generally more advanced than the controls from Spain, the results of this study suggest that ubiquitylation and sumoylation are not associated with the progression of renal cell carcinoma.…”
Section: Renal Tumorsmentioning
confidence: 99%